Statics study pack free-body diagram workbook & chapter reviews - Schiavone, Peter (Pearson/Prentice Hall, 2008)
Free body diagram worksheets and chapter reviews for Engineering Mechanics Statics Fifth Edition. Also includes MATLAB and Mathcad tutorials.